Comment: Mapping Neutrality Within the Affective Landscape: A Response to Yih, Uusberg, Qian, and Gross. (January 2020) - Gasper, Karen; Hu, Danfei
Yih, Uusberg, Qian, and Gross (2019) proposed an appraisal approach to help conceptualize five different states that researchers have used as neutral control conditions. This approach has the potential to enrich our understanding of these states and how they function. Here, we discuss four points to keep in mind while implementing this approach with the hope that these ideas will further assist researchers in understanding how neutrality might fit within the affective landscape.